1983
DOI: 10.1680/geot.1983.33.3.307
|View full text |Cite
|
Sign up to set email alerts
|

Static and dynamic lateral deflexion of piles in non-homogeneous soil stratum

Abstract: The Paper presents the results of a systematic parametric investigation of the static and dynamic response of single free-head piles embedded in a soil stratum, the modulus of which increases linearly with depth. The study is conducted by means of a dynamic finite-element formulation which accounts for the three-dimensionality of soil deformation while properly reproducing the radiation damping characteristics of the system. The soil is modelled as a linear hysteretic continuum and the excitation consists of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…It can also be concluded here that many piles, which exhibit a flexible (length-independent) static behaviour cannot be considered as flexible under dynamic loads at frequencies near resonance. Results of finite element studies carried out by Krishnan et al (1983) also leads to a similar conclusion that the active pile length increases significantly under dynamic load.…”
Section: Bending Momentsupporting
confidence: 59%
See 1 more Smart Citation
“…It can also be concluded here that many piles, which exhibit a flexible (length-independent) static behaviour cannot be considered as flexible under dynamic loads at frequencies near resonance. Results of finite element studies carried out by Krishnan et al (1983) also leads to a similar conclusion that the active pile length increases significantly under dynamic load.…”
Section: Bending Momentsupporting
confidence: 59%
“…However, the field dynamic lateral load tests carried out at sites predominantly consists clay and sandy clay layers by various authors (Novak 1985;Blaney and O'Neill 1986;Nogami et al 1992;Puri and Prakash 1992;Dou and Byrne 1996;Anandarajah et al 2001;Pak et al 2003;Boominathan and Ayothiraman 2006) show large discrepancy between observed and estimated values due to nonlinear behaviour of soil and gapping at the pile-soil interface. Kuhlemeyer (1979), Angelides and Roesset (1981), Krishnan et al (1983) and Wu and Finn (1997) attempted to study the dynamic soil-pile interaction problem considering nonlinear behaviour of soil adopting finite element method (FEM). Though the FEM is a powerful method, a rigorous threedimensional finite element analysis of dynamic soil-pile interaction is computationally intensive and expensive too.…”
Section: Notations Dmentioning
confidence: 99%
“…It does not account for non-linear soil behaviour and inertial loading effects arising from seismic soil-pile interaction that affect the bending moment response along the pile. Krishnan et al (1983) proposed an effective length for single free-head piles embedded in a soil stratum whose modulus increases linearly with depth. Their length criterion was based on the maximum pile head deflection and expressed as a function of only the relative pile-soil stiffness.…”
Section: Active Lengthmentioning
confidence: 99%
“…They used a 3D FE formulation for the developing soil reactions against pile displacements. An alternative approximate 2D plane-strain model, presented by Gazetas and Dobry14 assumes that compression-extension waves propagate in the two quarter-planes along the direction of loading while shear waves are generated in the two quarter-planes perpendicular to the direction of loading [ Figure 4 (13) where ull is given by equation (11) and I)@, 19) is the attenuation function (still to be determined). It is sufficient to compute I)(r, 0) only for 0 = 0 and 0 = n/2 and then use the approximation $(r, e) z $(r, 0) cos2 e + I) I , -sin2 e to obtain a very good estimate for any arbitrary angle il.2*7, 28 The following approximate expressions for $(r, 0) and $(r, n/2) have been developed in Reference [S]:…”
Section: Problem Definitionmentioning
confidence: 99%